ANALYSIS OF THE OPTIMAL PORTFOLIO OF THE SINGLE INDEX MODEL ON BANKING SUBSECTOR STOCKS IN THE LQ45 INDEX AT THE BEI FOR THE 2019-2024 PERIOD - Fahrudin, Alya Septiya; Aminda, Renea Shinta; Hurriyaturrohman (Manager : Jurnal Ilmu Manajemen, 2025)
This investigation seeks to identify the optimal portfolio, measure the potential return and risk of stocks, and determine the appropriate fund allocation proportions for Subsection of the banking sector stocks Belonging to the LQ45 Index. The research employs the Single Index Model, which assumes that security returns move in correlation with the market index. A purposive sampling method was used to select the research samples. As a result, five companies were included in the analysis: PT Bank Negara Indonesia (Persero) Tbk (BBNI), PT Bank Central Asia Tbk (BBCA), PT Bank Tabungan Negara (Persero) Tbk (BBTN), PT Bank Mandiri (Persero) Tbk (BMRI), and PT Bank Rakyat Indonesia (Persero) Tbk (BBRI). Of these, only three stocks BBCA, BMRI, and BBNI qualified for inclusion in the optimal portfolio. The highest fund allocation was given to BBCA at 78%, followed by BMRI at 21%, and BBNI with the smallest proportion at 1%. The expected return of the constructed portfolio is 0.00900, with a corresponding risk level of 0.0563.